Two new species of Kapateira Young from Costa Rica (Auchenorrhyncha: Cicadellidae: Cicadellinae) - Godoy, Carolina; Garita-Cambronero, Jerson; Rivera, Carmen; Villalobos, William (Zootaxa, 2006)
The genus Kapateira was described by Young (1977), who included one species from Colombia but noted that the genus also occurs in Panama, Venezuela, Eucador, and Bolivia. In this paper two new species are decribed, K. peruana from Peru and K. coffea from Costa Rica. The latter species is associated with coffee and citrus, and information is provided on its biology. DAS-ELISA tests for the bacterium, Xylella fastidiosa, yielded numerous positive results, suggesting that K. coffea is a potential vector of diseases such as coffee leaf scorch and citrus variegation chlorosis.